The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/14733315.2017.1377393
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation performance and indoor air pollutants diagnosis in 21 French low energy homes

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The healthy IAQ requirements and energy-efficient buildings are a strictly related challenge studied by several researchers [124][125][126][127][128][129]. IAQ monitoring and assessment should be considered as an efficient and effective method to support decision making while designing enhanced living environments in energy-efficient buildings [130]. The increase of IAQ monitoring systems leads to the development of potential energy-efficient methods to promote IAQ.…”
Section: Resultsmentioning
confidence: 99%
“…The healthy IAQ requirements and energy-efficient buildings are a strictly related challenge studied by several researchers [124][125][126][127][128][129]. IAQ monitoring and assessment should be considered as an efficient and effective method to support decision making while designing enhanced living environments in energy-efficient buildings [130]. The increase of IAQ monitoring systems leads to the development of potential energy-efficient methods to promote IAQ.…”
Section: Resultsmentioning
confidence: 99%
“…If not cleaned, dust covering the grille flaps decreases airflow, especially for the low openings of the grille [12]. The average in-situ drift of the hygroscopic devices after 9 years of operation is estimated below ± 1.5 %RH and is lower than the announced accuracy of the electronic humidity sensors at installation (± 1.8 %RH) [13].…”
Section: 2humidity Based Demand-controlled Ventilation Systemsmentioning
confidence: 99%
“…1,3,6,7 Statistical analysis of such large-scale measurements can then help to determine the influence of building and occupant characteristics. For example, differences have been observed between apartments and houses, 6 ventilation systems, [8][9][10][11] ventilation rates, 1,6,[12][13][14] or dwellings with gas cookers, 3 renovations, 15 smokers or even the additional emissions associated with the storage of paints and cleaning materials within attached garages. 1 Significantly, these studies have indicated the influence upon IAQ of occupancy and human activity, 1,16,17 the presence of indoor sources of pollutants, 3,10,18 and ventilation rates.…”
Section: Introductionmentioning
confidence: 99%